2019
DOI: 10.1021/acs.jpclett.9b03046
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Engineering in MASnBr3 and CsSnBr3 Perovskites: Mechanistic Insights through the Application of Pressure

Abstract: Here we report on the first structural and optical high-pressure investigation of MASnBr3 (MA = [CH3NH3]+) and CsSnBr3 halide perovskites. A massive red shift of 0.4 eV for MASnBr3 and 0.2 eV for CsSnBr3 is observed within 1.3 to 1.5 GPa from absorption spectroscopy, followed by a huge blue shift of 0.3 and 0.5 eV, respectively. Synchrotron powder diffraction allowed us to correlate the upturn in the optical properties trend (onset of blue shift) with structural phase transitions from cubic to orthorhombic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 39 publications
7
63
0
1
Order By: Relevance
“…These results highlight the impact of different A-cations on the pressure response. 20 Triggered by these results, clearly correlating the observed trends to local lattice properties, we extended the HP study to FASnBr 3 by virtue of its peculiar structural features, and also to confirm the mechanistic picture we obtained on MASnBr 3 and CsSnBr 3 . 20,21 Previously, we reported that FASnBr 3 is characterized by a distorted structure with partly uncoupled SnBr 3 units, and that its 3D structure originates from a dynamical averaging of quasi-0D structures.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…These results highlight the impact of different A-cations on the pressure response. 20 Triggered by these results, clearly correlating the observed trends to local lattice properties, we extended the HP study to FASnBr 3 by virtue of its peculiar structural features, and also to confirm the mechanistic picture we obtained on MASnBr 3 and CsSnBr 3 . 20,21 Previously, we reported that FASnBr 3 is characterized by a distorted structure with partly uncoupled SnBr 3 units, and that its 3D structure originates from a dynamical averaging of quasi-0D structures.…”
Section: Introductionsupporting
confidence: 74%
“…20 Triggered by these results, clearly correlating the observed trends to local lattice properties, we extended the HP study to FASnBr 3 by virtue of its peculiar structural features, and also to confirm the mechanistic picture we obtained on MASnBr 3 and CsSnBr 3 . 20,21 Previously, we reported that FASnBr 3 is characterized by a distorted structure with partly uncoupled SnBr 3 units, and that its 3D structure originates from a dynamical averaging of quasi-0D structures. 21 Such structural characteristics make FASnBr 3 a useful system to probe the extent of pressure effects on the electronic structure and to correlate these effects to local metal-halide bond distances.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations